FOR THE LOVE OF GOD’S WORD: AN INTRODUCTION TO BIBLICAL INTERPRETATION - C. Stenschke (Acta Theologica)
Review of the book: Andreas J. Köstenberger, Richard D. Patterson, (Grand Rapids: Kregel Academic; Edinburgh: Alban Books, 2015). 444 pp., hardbound. ISBN 978-0-8254-4336-7, 24 USD.